2015
DOI: 10.1016/j.niox.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute dietary nitrate intake on maximal knee extensor speed and power in healthy men and women

Abstract: Nitric oxide (NO) has been demonstrated to enhance the maximal shortening velocity and maximal power of rodent muscle. Dietary nitrate (NO3-) intake has been demonstrated to increase NO bioavailability in humans. We therefore hypothesized that acute dietary NO3- intake (in the form of a concentrated beetroot juice (BRJ) supplement) would improve muscle speed and power in humans. To test this hypothesis, healthy men and women (n=12; age=22-50 y) were studied using a randomized, double-blind, placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
185
7
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(230 citation statements)
references
References 39 publications
28
185
7
2
Order By: Relevance
“…It is therefore possible that elevated type II muscle Ca 2+ handling and muscle contractile function may have further contributed to the improved 1500 m performance observed in the present investigation. Furthermore, several recent studies have observed improvements in physiological functioning and exercise performance in situations where type II muscle recruitment is likely to be high (Breese et al 2013;Bailey et al 2015;Coggan et al 2015), which further supports the findings of this investigation.…”
Section: Effects Of Brj On 1500 M Tt Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…It is therefore possible that elevated type II muscle Ca 2+ handling and muscle contractile function may have further contributed to the improved 1500 m performance observed in the present investigation. Furthermore, several recent studies have observed improvements in physiological functioning and exercise performance in situations where type II muscle recruitment is likely to be high (Breese et al 2013;Bailey et al 2015;Coggan et al 2015), which further supports the findings of this investigation.…”
Section: Effects Of Brj On 1500 M Tt Performancesupporting
confidence: 90%
“…These effects, which were reported in predominantly type II muscle, were accompanied by an increased muscle force production. Subsequent studies have confirmed the beneficial effect of NO 3 − on force production in humans (Haider and Folland 2014;Coggan et al 2015). It is therefore possible that elevated type II muscle Ca 2+ handling and muscle contractile function may have further contributed to the improved 1500 m performance observed in the present investigation.…”
Section: Effects Of Brj On 1500 M Tt Performancesupporting
confidence: 70%
See 1 more Smart Citation
“…Further, there is evidence from murine model investigations that nitrate supplementation may enhance tissue blood flow [41,42] and muscle contractile function [9] preferentially in type II muscle fibres. It is therefore possible that nitrate supplementation is more effective during shorter more high-intensity exercise, during which these muscle fibres are more heavily recruited [9,[43][44][45]64], or else in individuals with greater distribution of type II muscle fibres [43]. The time-trial duration employed in this study (< 6 minutes) was considerably less than other investigations (~ 17 -48 minutes) which have not observed an ergogenic effect of nitrate supplementation in hypoxia [38][39][40], and may be important.…”
Section: Effect Of Nitrate Supplementation On Running Performance In mentioning
confidence: 76%
“…Similarly, increased evoked contractile force has been observed in human skeletal muscle in vivo during low-frequency submaximal stimulation and over the initial stages of high-frequency maximal stimulation following NO 3 Ϫ supplementation (31). However, NO 3 Ϫ ingestion has been shown to increase human peak knee extensor torque at 360°/s, but not 90°/s, 180°/s, and 270°/s, in vivo (15). Collectively, these findings suggest that dietary NO 3 Ϫ supplementation enhances skeletal muscle contractile function, and that it might be particularly effective at augmenting contractility at higher contraction velocities.…”
mentioning
confidence: 70%